2017
DOI: 10.1021/acsnano.7b05083
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Kidney Exosome Analysis for the Detection of Kidney Transplant Rejection

Abstract: Kidney transplant patients require life-long surveillance to detect allograft rejection. Repeated biopsy, albeit the clinical gold standard, is an invasive procedure with the risk of complications and comparatively high cost. Conversely, serum creatinine or urinary proteins are noninvasive alternatives but are late markers with low specificity. We report a urine-based platform to detect kidney transplant rejection. Termed iKEA (integrated kidney exosome analysis), the approach detects extracellular vesicles (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 25 publications
(48 reference statements)
0
91
0
Order By: Relevance
“…Based on the assumption that the exosomes released by immune cells into urine can serve as surrogate biomarker for kidney transplant rejection, a screen was conducted to identify markers specific to the immune cell‐derived exosomes. The results show that CD3 is the most effective marker for distinguishing patients that have a high propensity to reject transplant from non‐rejection patients …”
Section: Exosome Signaling Methodsmentioning
confidence: 99%
“…Based on the assumption that the exosomes released by immune cells into urine can serve as surrogate biomarker for kidney transplant rejection, a screen was conducted to identify markers specific to the immune cell‐derived exosomes. The results show that CD3 is the most effective marker for distinguishing patients that have a high propensity to reject transplant from non‐rejection patients …”
Section: Exosome Signaling Methodsmentioning
confidence: 99%
“…In particular, urinary EVs released from the epithelium of different nephron segments could serve as biomarkers of diverse pathological states and response to therapeutic agents [5]. Previous reports demonstrated that EVs derived from speci c immune cells and EVs carrying innate immune proteins can be detected in the urine after kidney transplantation [17,18]. Thus, in the present study we characterized populations of urinary EVs derived from activated immune cells in CSFs compared to NSFs (controls).…”
Section: Introductionmentioning
confidence: 90%
“…The presence of intragraft infiltration of T-cells is one of the hallmarks for the diagnosis of acute cellular rejection after kidney transplantation. A recent study has shown the higher level of CD3-positive urinary exosomes in patients with acute cellular rejection that could reflect T-cell infiltration in the renal allografts (Park et al, 2017). Similarly, a subsequent proteomics study has demonstrated the increased levels of urinary exosomal tetraspanin-1 and hemopexin in patients with T-cell-mediated rejection (Lim et al, 2018).…”
Section: Kidney Transplantationmentioning
confidence: 99%